2019
DOI: 10.1371/journal.pone.0219181
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal bacterial supernatants modify differentiation, migration and inflammatory cytokine expression in human periodontal ligament stem cells

Abstract: Periodontal ligament stem cells (PDLSC) play an important role in periodontal tissue homeostasis/turnover and could be applied in cell-based periodontal regenerative therapy. Bacterial supernatants secreted from diverse periodontal bacteria induce the production of cytokines that contribute to local periodontal tissue destruction. However, little is known about the impact of whole bacterial toxins on the biological behavior of PDLSC. Therefore this study investigated whether proliferation, migration, inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…This suggests that hPDLSCs could be useful in therapy of periodontal diseases by regeneration, reconstruction, and fixation of periodontal tissue [8]. Recent studies have demonstrated that endotoxins produced by periodontal pathogens can disrupt microenvironment homeostasis and destroy periodontal tissue through suppressing the viability of hPDLSCs [4,9]. Periodontal inflammation plays important roles in progression of periodontitis, but the underlying mechanism of pathogenesis remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that hPDLSCs could be useful in therapy of periodontal diseases by regeneration, reconstruction, and fixation of periodontal tissue [8]. Recent studies have demonstrated that endotoxins produced by periodontal pathogens can disrupt microenvironment homeostasis and destroy periodontal tissue through suppressing the viability of hPDLSCs [4,9]. Periodontal inflammation plays important roles in progression of periodontitis, but the underlying mechanism of pathogenesis remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated periodontitis is related to systemic conditions such as cardiovascular disease, diabetes mellitus, adverse pregnancy outcomes, and osteoporosis [3]. Periodontitis is related to immune reactions and is affected by exposure to endotoxins from Gram-negative bacterial species in the dental biofilm [4]. Currently, there are still no clinically effective therapeutic strategies for periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…gingivalis . Indeed, with human periodontal and immune cells, CSP stimulates pro‐inflammatory characteristics, such as induction of inflammation‐related receptor expression and pro‐inflammatory cytokine secretion [18–21], all of which contribute to the virulence of this bacterium. However, whether CSP also stimulates pro‐inflammatory characteristics with the alveolar epithelium has not been reported.…”
mentioning
confidence: 99%
“…These cells were described as an excellent cell source owing to their ease of accessibility, their ability to differentiate into osteoblasts and odontoblasts and lack of ethical controversies (45). Moreover, dental stem cells demonstrated superior abilities in immunomodulation properties either through cell to cell interaction or via a paracrine effect (46). Stem cells of non-dental origin were also suggested for dental tissue and bone regeneration.…”
Section: Stem Cells In Dentistrymentioning
confidence: 99%